IMPLEMENTASI SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB (STUDI KASUS : SMK DR INDRA ADNAN INDRAGIRI COLLAGE) - Muhammad Bambang Iswanto; Ilyas; Fitri Yunita (Indragiri Islamic University, 2022)
Education is very important for everyone. Education is generally defined as a life process in developing each individual to develop and be able to live. The first time we get education in the family, school and community environment, in schools without students, an educational institution cannot carry out its function to provide educational services to the community. Every educational institution seeks to acquire students every new academic year through the acceptance of new students, especially SMK Indra Adnan Indragiri COLLEGE, based on this, a web-based information system for new student admissions is needed. In the pandemic, it is very necessary to accept online-based new students in its development, the Waterfall method was chosen as a flow of thought and for analysis using PIECES, in system design using UML (Unified Modeling Language). With the implementation of this web-based new student admissions information system, it aims to provide convenience in accepting new students so that they can be widely reached and follow the current era.